Principal Instructional Leadership, Teacher Self-Efficacy, and Teacher Professional Learning in China: Testing a Mediated-Effects Model - Shengnan Liu (2019)
© The Author(s) 2018. Background: Empirical evidence increasingly suggests that leadership which motivates, supports, and sustains the professional learning of teachers has a knock-on effect for both student learning and school improvement. The current study was conducted in China, where the workplace learning of teachers is embedded in a strong tradition of school-based, teacher learning practices such as the Master Teacher–Apprentice Bond and Teacher Research Groups. Purpose: The study investigated a mediated-effects model of principal instructional leadership and teacher learning. The model proposed principal time management skills and self-efficacy as antecedents of instructional leadership and teacher self-efficacy as a mediator of principal instructional leadership effects on the professional learning of teachers. Method: Survey data were collected from 3,414 teachers and 186 principals in 186 middle schools in Qingdao, China. Confirmatory factor analysis, structural equation modeling, and bootstrapping were used to analyze the multisource data. Results: The research confirmed a partial mediation model whereby principal instructional leadership evidenced moderate direct and indirect effects on teacher professional learning. Principal time management and self-efficacy exercised small effects on principal instructional leadership. Implications: The research adds to a growing body of research that affirms a positive relationship between principal leadership and teacher professional learning and emphasizes the importance of self-efficacy in shaping educator practice. The authors suggest the timeliness for scholars to undertake systematic reviews of this literature on leadership and teacher professional learning, and offer recommendations for school leadership practice.